2014
DOI: 10.1177/0022034514554225
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Indicators of Implantation Success of Tissue-Engineered Oral Mucosa

Abstract: Real-time (RT) determination of the health of in vitro tissue-engineered constructs prior to grafting is essential for prediction of success of the implanted tissue-engineered graft. In addition, the US Food and Drug Administration requires specific release criteria in RT prior to the release of tissue-engineered devices for human use. In principle, assessing the viability and functionality of the cellular component can be achieved by quantifying the secretion of growth factors and chemokines of tissue-enginee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Khmaladze and coworkers recently proposed a non‐invasive method that allows real‐time monitoring of the thermal stress, and therefore the viability, of the EVPOME before implantation . The same group demonstrated that high levels of interleukin‐8 (IL‐8), human β‐defensin I (hBD‐I) and tissue inhibitor of metalloproteinase 2 (TIMP‐2) were predictors of healthy EVPOME . Nevertheless, further clinical studies are needed, as this method appears promising not only for distinguishing stress and non‐stressed EVPOME before implantation but also for evaluating post‐grafted outcomes …”
Section: Keratinocyte‐based Constructsmentioning
confidence: 99%
“…Khmaladze and coworkers recently proposed a non‐invasive method that allows real‐time monitoring of the thermal stress, and therefore the viability, of the EVPOME before implantation . The same group demonstrated that high levels of interleukin‐8 (IL‐8), human β‐defensin I (hBD‐I) and tissue inhibitor of metalloproteinase 2 (TIMP‐2) were predictors of healthy EVPOME . Nevertheless, further clinical studies are needed, as this method appears promising not only for distinguishing stress and non‐stressed EVPOME before implantation but also for evaluating post‐grafted outcomes …”
Section: Keratinocyte‐based Constructsmentioning
confidence: 99%
“…Allopatch scaffolds were rehydrated in DPBS for 1.5 hr in the initial protocol but were rehydrated in DPBS overnight for optimized procedures to manufacture EVPOMEs using Allopatch based on the results of the diffusion pattern analysis. The manufacturing of EVPOMEs was reported previously (Izumi et al, ; Izumi, Song, & Feinberg, ; Kuo et al , ). Briefly, 200,000 oral keratinocytes/cm 2 were seeded on 1 cm‐diameter acellular Allopatch and AlloDerm® scaffolds that were presoaked in 0.05 μg/μl human Type IV collagen (Sigma‐Aldrich, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The University of Michigan Institutional Review Board approved all procedures of harvesting human oral mucosal and skin tissues. The procedures for culturing primary human oral and skin keratinocytes were described previously (Bayar et al, ; Kuo et al, ). Briefly, primary human oral and skin keratinocytes were enzymatically dissociated using 0.04% and 0.125% trypsin (Sigma‐Aldrich, St. Louis, MO, USA), respectively, from the tissue samples, and cell cultures were established in serum free chemically defined culture medium (EpiLife and EDGS, Life Technologies, Grand Island, NY, USA) containing 0.06 mM calcium, 25 μg/ml gentamicin, and 0.375 μg/ml fungizone.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations